Study of bicycle movements on shared footways - Leow, Bok Wee. (2009)
Cycling is becoming increasingly popular in Singapore nowadays, and more people are using it as a form of transport for short trips to train stations and town centres. Worldwide, many countries are promoting cycling as a cleaner and greener way of travelling to combat the ever worsening problem of pollution. Unfortunately, land scarce Singapore has, in the past, not given cycling high priority in developing its transport network, and most cyclists have to share the same right-of-way either with pedestrians on a footway or vehicles on a roadway.